ANTI-OBESITY NUTRACEUTICALS: INSIGHTS INTO MECHANISMS OF ACTION AND POTENTIAL USE OF BIOCOMPATIBLE NANOCARRIERS FOR DELIVERY - ABDELFATTAH, DOAA SALAH ELDIN; FOUAD, MERVAT A.; ELMESHAD, ALIAA N.; El-NABARAWI, MOHAMED A.; ELHABAL, SAMMAR FATHY (International Journal of Applied Pharmaceutics, 2024)
One of the serious health issues that has detrimental effects on health is obesity. Obesity is associated with common comorbidities like diabetes, dyslipidemia, and cardiovascular diseases. New understanding of the pathophysiologic mechanisms underlying obesity has led to the development of several novel agents and effective strategies to combat the global obesity epidemic and its comorbidities. The objective of managing obesity has changed to include both reducing its complications and helping people lose weight. Although there are more pharmaceutical options available for managing obesity, their efficacy and safety profiles are either limited or moderate. While behavior interventions and active lifestyle remain the cornerstones of successful weight loss, it can be very challenging to maintain such a healthy lifestyle. Thus, new agents that are safer and more effective are therefore urgently needed. Natural products and dietary supplements have been demonstrated as a potential treatment for obesity. Recent studies suggested that propolis, chromium picolinate, and White Kidney Bean Extract (WKBE) may have anti-obesity properties. This review provides an overview on the anti-obesity effects of these natural products, their active ingredients and mechanisms of action. In addition to potential cutting-edge delivery techniques that can be applied to maximize the anti-obesity effects of these bioactive substances with varying solubility, bioavailability, and stability.